Lifetime Health Care Costs of the Danish Population - Jan Sørensen; Rikke Søgaard (Journal of Health Economics and Outcomes Research)
**Objectives:** Lifetime health care cost is a statistical indicator for expected health care use during the remaining lifetime of an individual. The objective of this study was to estimate the lifetime health care costs for individual gender and age strata.